Race, gender, and comedy awards: from civil rights to color-blindness. Issue 1 (2nd January 2017) - Pérez, Raúl
ABSTRACT: Racial/ethnic and gender diversity played an important role in the development of stand-up comedy in the US from the civil rights era to the present. Many of the most visible and celebrated comedians during this period (e.g. Lenny Bruce, Bill Cosby, Richard Pryor, Joan Rivers, Margaret Cho) were critical in shaping and popularizing this culture industry we are most familiar with today. This paper examines the racial and gender demographic trends of winners and nominees in the Grammy Award for 'Best Comedy Album'. This award is the longest running prize for commercial comedy in the US, from 1959 to 2015. Here, I measure the cultural impact of the civil rights movement on this comedy award by analyzing race and gender trends of exclusion and inclusion throughout the award's history. I find the civil rights movement had a significant impact on racial inclusion (but not gender) until the mid-1980s. Moreover, while the current data suggests there is greater gender diversity in recent years, it also illustrates a trend toward racial exclusion. I contend that cultural prizes, while ostensibly awarding merit and excellence, are key public sites that reproduce racial inequality in the current 'color-blind' and 'post-racial' era.